The Effect of Talent Management on Employee Performance at Bank BTN Bandung - Noorhan, Elly Watti; Agustina, Granit; Ahmadi, Rudi Suprianto; Febrian, Feby (International Journal of Psychosocial Rehabilitation, 2020)
In this study there are two variables, namely variable X (talent management) and Y variable (performance). This research was conducted to determine the effect of Talent Management on Employee Performance at Bank BTN Bandung. The method used in this study is a descriptive analysis method to identify how the influence of talent management and how much employee performance at Bank BTN Bandung. While the verification of analysis to identify problems is how much influence Talent Management has on the Performance of Bank BTN Employees. This research was conducted at the Bank BTN Bandung office. This research was conducted using a sample based on Purposive Sampling. The hypothesis of this research is Talent Management influences Employee Performance at Bank BTN Bandung. To measure the effect of these variables using Simple Linear Regression with the help of the application software system SPSS 21.0. Based on the results of data analysis using statistical methods, it was concluded that there was a significant influence between Talent Management on Performance, this was based on regression analysis with the equation Y = 3,588 + 0.293X. In correlation there is a fairly strong or moderate relationship between Talent Management and Bank Employee Performance with a value of 0.543 Furthermore, it is obtained the coefficient of determination (KD) that Talent Management affects Performance with a value of 29.5%. Hypothesis testing of this study in which the tcount of 4.927 is greater than the value of t table 1.670 Then H1 is accepted and H0 is rejected, which means that Talent Management influences Employee Performance.